Association between Vitamin D Receptor Gene Foki Polymorphism and Gestational Diabetes Mellitus among Iraqi Pregnant Women - Raya Hatem Al-Mawla1 , Hameed Hussein Ali2 , Wajeeh Younis Al-Ani2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was conducted to evaluate the association between vitamin D receptor gene FokI polymorphismand gestational diabetes Mellitus (GDM) among Iraqi pregnant women.This study included 40 women with GDM, 30 pregnant women without GDM, and 30 non-pregnant womenas a negative control. Age (years), body mass index (BMI), Fasting Blood Glucose (FBG), total cholesterol,triglycerides (TG), and lipid profile of the patients and control groups were compared (Table 1). DNAsampling was purified and amplified by using PCR. The FokI genotype was evaluated using restrictionfragment length polymorphism (RFLP).The results revealed that the age, BMI, FBG, HbAIc, insulin hormone, insulin resistance, and lipid profileexcept HDL-C were significantly increased with an increased GDM risk compared to women with normalpregnancies. In contrast, no significant alterations were observed in concentrations of IGF1 hormone,vitamin D and FokI (F and f) alleles frequency between GDM and control groups.This study suggests that there was no significant correlation between the VDR FokI polymorphism andGDM patients among Iraqi pregnant women.